Susceptibility of Streptococcus agalactiae to erythromycin and clindamycin in pregnant women in the prenatal screening - Araújo, Max Roberto Batista; Reis, Poliane Vieira; Nascimento Bicalho, Patrícia Helena; Seabra, Luisa Ferreira (Clinical and Biomedical Research, 2019)
Introduction: Group B streptococcus (GBS), or Streptococcus agalactiae, is a bacterium found in normal human microbiota. However, it may cause neonatal pneumonia, sepsis, and meningitis. Genital colonization in pregnant women is associated with a higher risk of preterm birth. The treatment of choice is antibiotic therapy with beta-lactams, but in the case of multidrug-resistance, erythromycin and clindamycin can be used. Methods: This study evaluated bacterial cultures in the period from 2014 to 2015 from a group of 29,875 pregnant women. GBS colonization and resistance to erythromycin and clindamycin were investigated. Results: Positive cultures were found in 26.8% and 26.1% of the samples in 2014 and 2015, respectively. Levels of resistance to erythromycin and clindamycin were, respectively, 2.4% and 5.5% in 2014 and 3.2% and 6.5% in 2015. Conclusion: The investigation of GBS colonization and the evaluation of GBS resistance to erythromycin and clindamycin are of extreme relevance, given the increasing incidence of bacterial resistance, risks of preterm birth, and serious consequences to newborns, representing a global health problem. Keywords: Streptococcus agalactiae; erythromycin; clindamycin; prenatal care; drug resistance, microbial